Вы находитесь на странице: 1из 24

181

6.
, ,
, , . . ,
.
, . . .
.
6.1.
. 6.1 1 2 dl.
p. gpdl. 1 2 ,
+ d.

V2 = V + d V

T
+d

2
dl
H

1
V1= V

gpdl

x
. 6.1.

, , . .
V1 + gpdl V2 = 0.

(6.1)

, , H, 1 2, .
V1 = V , V2 = V + dV (6.1),
V + gpdl V dV = 0,

dl =
, V = HU ,

1
dV .
gp

dV = HdU .
H
dl =
dU .
gp

(6.2)

182

,
l=

x2

1 + U 2 dx [31].

x1

dl = dx 1 + U 2 .

(6.3)

(6.2) (6.3)
H
gp
dU
dU = 1 + U 2 dx;
dx =
,
gp
H
1 + U 2
x=

H
dU
H
H
=
ln U + 1 + U 2 = arsh ( U ) + C1 .

2
gp 1 + U
gp
gp


gp
( x + C1 ) = ln U + 1 + U 2 = arsh U .
H

gp
( x + C1 ) ,
H

U = sh
U=

(6.4)

H
gp
ch
( x + C1 ) + C2 .
gp
H

(6.5)

, (6.5) . , .
, , ( 6.2). , .
l
U

-x

. 6.2.

, x = 0; U = 0: C1 = 0 ; x = 0; U = 0: C2 =

H
.
gp

183

U=

H
gp

x 1 ;
ch

gp
H

(6.6)

gp
x.
H

(6.7)

U = sh

. 6.3 , p = 16 -1,
l = 600 , H = 200000 (U(x)) H1 = 400000 (U1(x)),.
36,173 18,02 .

. 6.3.

(6.6),
, [55].
, . ,
gp l
l
l

x = ; U = 0 . (6.4): 0 = sh
+ C1 ; C1 = . x = 0, U = 0 (6.5)

H 2
2
2

0=

H
gp l
H
gpl
ch
.
+ C2 ; C2 = ch gp
H 2
gp
2H
x

x = l/2

y
. 6.4.

U =

H gpl
gp
l
ch
ch x ,

gp 2 H
H
2

(6.8)

184

gp
l
x .
H
2

U = sh

(6.9)


1 gp 2 x2 +l

2
H
1
e

x2

l=

1 + U 2 dx =

x1

1
H
2

pe

gp ( 2 x2 + l )
[
]
2H

He
2

2
gp

2 H ( 2 x1 + l )

gpe

gp

( 2 x1 + l )
2H

(6.10)

,
, U = f
l
x = , . .
2
f =

H gpl
ch
1 .
gp 2 H

(6.11)

- , ( ).
, ,
. , , . . 6.5
. l.
l/2

l/2

-x
a

. 6.5. . O

l, ,
, h .
a b, O . : UA
- UB = h , a + b = l.
(6.6)

185

U A UB =

H gp
H gp

ch ( a ) 1
ch b 1 .

gp H
gp H


b g p
H ag p
ch
= h,
ch
H
H
gp
a + b = l.

(6.12)

(6.12) . ,
,
h=

H
1 a g p b g p
1 b g p a g p
2 sh
+

sh
=

gp
2 H
H
2 H
H

gp
H gp
( a + b) sh
( a b)
=2
sh

g p 2H
2H

gp
gp l
( a + b) = sh
.
2H
2H
g pl
g pl
x (l ) = sh
U (l ) =
.
2H
2H
g pl
, sh
,
2H
a + b = l , sh

g pl g pl 1 g pl
sh

+
.
2H
2 H 48 H
gp = 160 H; H = 200000 H; l = 600 , 0,24,
6,410 -9.
h = l sh

gp
( a b) .
2H

ba =

2H
h
arsh ,
gp
l

a b
2H
h

arsh ;
a b =
gp
l

a + b = l.

(6.13)

186

a=

l
H
h H
h
+
arsh =
+ arsh ,
2 gp
l g p
l

b=

l
H
h H

arsh =
arsh
2 gp
l g p

(6.14)

h
.
l

(6.15)

g pl
- , 2H
.
(6.15) :
h
> arsh - ;
l
h
= arsh - ;
l
h
< arsh - .
l
h
, , ( = arsh
l
), . 6.6.
=

l
A

h /2

B
0

l/2
a

. 6.6.

, . . h,
g pl
h g pl
, arsh =
. h = l sh
.
l 2H
2H
qgp l
h
h
< arsh
= arctg .
, 2H
l
l
, . . (. 6.8).

187

h /2

B
l
b

a
. 6.7.

. 6.8 (6.13)
2H
h

arsh ;
a + b =
gp
l

a b = l.

(6.16)

a b

a =

b =

H
h
+ arsh ;
g p
l
H
h

arsh .

g p
l

(6.17)

, h
U 2 ( x1 ) = x1 , , l

H g p
H gp h
b + x1 ) 1
b 1 x1 =
(
ch
ch
gp H
gp H l
g pb h
H gp
=
ch
b + x1 ) ch
x.
(

gp
H
H l 1

U ( x1 ) = U 1 ( x1 ) U 2 ( x1 ) =

(6.18)

6.1. , . h = 50 , = 45, H = 200000 H,


p = 16 -1.
g pl
h
h
50
=
= 50 , =
= 0,02, arsh = 0,881 , ,
h = 50 = 45, l =
tg tg 45
2H
l
l.
(6.17)

188
200000
( 0,02 + 0,881) = 1127;
160
200000
b=
( 0,881 0,02) = 1077.
160
a=

a = 1127 , (6.6)
H gpx
U ( x) =
ch
1 . 6.8.
g p H

. 6.8.
, 1077
H
p

1127 . U 1 x1 =
ch
b + x1 1 U ( b) .
gp
H

. 6.9. .

( )

. 6.9.
(6.18) , . 6.10.

. 6.10. .
h
U = 0,352 .
2

189
Lc = h 2 + l 2 = 70,711 .
(6.10)
l

Lm =

1 + U 1 dx1 =

2
gp

1 + sh
b + x1 dx =
H

H gp
gp
gp
gp
( b + l ) exp ( b + l ) exp b + exp b = 70,715 .
exp
2 p H
H
H
H

, , Lm - Lc
= 0,004 (4 ). , . . , (, ) .
6.2. : p = 16 -1, H = 200000 , h = 200 .
= 30. , .
l h = 200 = 30
l=

h
= 346,41 .
tg

Lc = h 2 + l 2 = 400 .

=

gpl
= 0,139;
2H

arsh

h
= 0,549.
l

h
> , (. 6.7). a b l
(6.17), (6.18)
. . arsh

a=

+ arsh = 859,838,
gp
l

b=

arsh = 513,428.
gp
l

H gp

ch
b + x1 1 U 1 (0) , .

gp H

6.11. , 30
.
,

U 1 ( x1 ) =

. 6.11

190

l
. 6.12. f = U1 = 13,6 .
2
(6.4)
U = sh

gp
x
H

x =b+

l
2

= 686,6 .

. 6.12.
U = 0,577 33 , . . , 33 , 30
.
( ) Lc = 400 .
(6.20)
a

Lm =

gp
1+
x dx = 401,281 .
H

, L = Lm - Lc = 1,281.

. L , .

6.2.

, ( , , ), ,
gp 2
(6.6), U =
x , [14, 52, 61, 79].
H
,
, p
x. , . 6.13.

191

T
U
2

U
gpx
H

x
x /2

x /2
x

. 6.13.

. 6.1 H T. ,
. 0 - 2 , 2, , . .

= HU g p x

x
= 0.
2


U=

gp 2
x .
2H

(6.3)
x2

Lm =

1 + U 2 dx.

x1

[31]

(1+ U )
R=
2

3
2

(6.19)
U =

gp
gp
x ,: U =
.
H
H

(6.19)

192

x2

Lm =

x1

1
p
1 + x d x =
g p x2 H 2 + g p 2 x22 +
H
2g pH

)]

(6.20)

+ H 2 ln g p x 2 + H 2 + g p 2 x 22 g p x1 H 2 + g p 2 x12 H 2 ln g p x1 + H 2 + g p 2 x12 ,
3

2
H g p 2 .
R=
1
+
x

g p H

(6.19) ,
(6.6)
3

H gp
1 g p 6
g p 2 1 g p 4
x 1
x +
ch
x +

x .
2H
g p
H
24 H
720 H
, x. U 3 ( x1 ) , . 6.11, . . 6.2,
6.4, ,
(. 6.5, 6.6) . 6.7.
,
a + b = l,
U A U B = h.
(6.19)
gp 2
( a b 2 ) = h;

2
H

a + b = l.

a b,
l hH
+
,
2 gl p
l hH
b=
.
2 gl p
a=

(6.21)

hH
.
gp
, ( 6.6) b = 0, a = l.
hH
l < 2
, .
gp
. 6.7
, l > 2

193

gp 2
( a b 2 ) = h,

2
H

a b = l .

,
l hH
+
,
2 gl p
l hH
b= +
.
2 gl p
a=

(6.22)

, , 2h H
hH

> l> 2
.
gp
gp
, (6.21) (6.22) a b
. .
U ( x) =

gp
g p 2 g p 2 g pb
( b + x) 2
b =
x +
x
2H
2H
2H
H

(6.23)


, , . .
U 3 ( x) = U ( x) U 2 ( x) =

gp 2
h
x + 2bx ) x ,
(
2H
l

gp 2 gp
gp
x
xl =
x( x l ) .
2H
2H
2H

(6.24)

1gp 2
l
, f =
l .
8 H
2
, f, (6.24)

x =

U 3 ( x) =

4f x
( l x) .
l2

(6.25)

6.10
6.12, , 6.1
6.2. . 6.14 6.15 , (6.24).

194

. 6.14

. 6.15

(. 6.14), , 6.1,
0,1 . ,
c 6.2 (. 6.15), 1,6 .
.
,

, .
6.3.

, , .
,
1 - 2 (. 6.16).
,
.

F ( x ,t)
2

+d

1
T
0

dx

x2

195

. 6.16.

,
, . F(x, t), .
(x, U)
, x.
x t U(x, t). , T, 1 2 . , (1-2) . (6.3)
l=

x2

x1

U
1+
dx.
x
2

U
x2 - x1 = dx, . .
,
x
2

U
U
.
1 >>
, =
x
x
, T
= U .
x t F(x, t), x (x, U). 1 - 2 Ox + d. .
U, 1 - 2
T sin ( + d ) T sin + F ( x , t ) dx.
sin =

tg
1 + tg
2

tg =

U
[38].
x

, 1 >> tg 2 ,
T tg ( + d ) T tg + F ( x , t ) dx =
U 2U
U
2U
= T
+
dx T
+ F ( x , t ) dx = T
dx + F ( x , t ) dx.
x
x2
x x2

p dx

2U
2U
=
T
dx + F ( x , t ) dx.
t2
x 2

2U
2U
=
pdx
,
t2
t 2

196

F ( x, t )
T
= a2 ,
= F , , p
p

dx

2
2U
2 U
=a
+ F,
t2
x2

(6.26)

a - , -1.
, a . .
F = 0, (6.26)
[59]. . . ,
, , . [59, 70, 79, 84].
(6.26) . U(x, t) , , (x = 0 x = l), ,
(t = 0). .
(, ) x = 0 x = l
,
U ( 0, t ) = 0;

U ( l , t ) = 0.

(6.27)

t = 0 , , (6.5), . . f (x).
,
(x).
,
U ( x , 0) = U t = 0 = f ( x ) ;

U
t t =0 = ( x) .

(6.28)

, f (x) = 0 (x) = 0, , , U(x, t) = 0.


6.3.1.
( )
( )
[59].

197

, (6.27) (6.28)
2
2U
2 U
, . .
=a
,
t2
x2
U ( 0, t ) = 0,
U ( l , t ) = 0,

U ( x ,0) = f ( x ) ,
U
= ( x ) .
t t =0
( ) ,
(6.27) X(x)
T(t), x, t:
U ( x , t ) = X ( x) T ( t ) .

(6.29)

(6.26) F = 0,
X ( x) T ( t ) = a 2 X ( x) T ( t )

T ( t )

a T( t )
2

X ( x)

X ( x)

(6.30)

, x, - , t.
(6.30) ,
, - k2, . .
T ( t )

a T( t )
2

X ( x)
X ( x)

= k 2 .


X ( x ) + k 2 x ( x ) = 0,
T ( t ) + k 2 a 2 T ( t ) = 0.

(6.31)
(6.32)

(6.31), (6.32) , ,
[24, 31] ( 3)
X ( x ) = A cos k x + B sin k x ,

(6.33)

T ( t ) = C cos k a t + D sin k a t ,

(6.34)

198

A, B, C, D - .
X(x) T(t) (6.29)
U ( x , t ) = ( A cos k x + B sin k x) ( C cos k a t + D sin k a t ) .

(6.35)

A (6.27), . .
U ( 0, t ) = 0,
U ( l , t ) = 0.
T(t) 0 , X(0) = 0, X(l) = 0.

0 = A + B 0,
0 = A cos k l + B sin k l .
= 0; sin k l = 0. 0, . . X(x) , sin k l = 0,
k=

j , ( j = 1, 2,...).
l

(6.36)

(6.33)
X j ( x ) = sin k j x .

(6.37)

X(x) , k . k, (6.34)
T (t ) = C cos a

j t + D sin a j t , ( j = 1, 2,...) .
l
l

(6.38)

(6.37) (6.38) (6.35) j, ,


kj ,

U j ( x , t ) = sin k j x C j cos a j t + D j sin a j t .

l
l

(6.39)

j Dj (6.28).
, j = CB Dj = DB. , (6.39)
,
n
a
j =
j A j sin
x , A j = C 2j + D 2j .
l
l
a
U1(x, t) 1 =
- l
; U2(x, t), U3(x, t)... a
a
2 =
2 , 3 =
3 ... .
l
l
,

199

. , . ( ,
).
(6.26) , (6.39)
, ,

U (x, t ) = U j (x, t ) ,
j =1

U j ( x , t ) = sin k j x C j cos a j t + D j sin a j t ,

l
l
j =1

(6.40)

(6.26), (6.27). , (6.40) (6.26)


, j Dj , , x t. (6.40)
(6.28).
Cj Dj. (6.40) t = 0, (6.28)

j x.
l

U ( x , 0) = f ( x ) = C j sin
j =1

(6.41)

, (6.35) t ,

U ( x, t )
a

= sin j x
t
l
l
j =1

j C j sin a j t + D j cos a j t .

l
l

(6.42)

t = 0,
U ( x , 0)
t

= ( x) = D j
j =1

a
jx.
l

(6.43)

f (x) (x) , (0, l) [59], (6.42) (6.43) ,


l

C j = f ( x ) sin j x d x ,
l 0
l
l

Dj

a
2

j = ( x ) sin j x d x ,
l
l 0
l

(6.44)

200
l

Dj =

( x ) sin j x d x .

a j 0
l

(6.45)

6.3. ,
6.1.
= 200000 . 6.10. U(x1)
. 6.17 (6.18) U1(x1) 1 = 300000 .

. 6.17.
, 1.
f ( x1 ) = U ( x1 ) U 1 ( x1 ) . 6.18.

. 6.18. f ( x1 ) = U ( x1 ) U 1 ( x1 )
, H = H1 H 2 , H.
, , ,
.

U ( 0, t ) = 0,
U ( l , t ) = 0.

U ( x , 0) = f ( x) = U 1 ( x1 ) U 2 ( x1 ),
U
t

= ( x) = 0.
t =0

201
, , (6.36)

k j = j ( j = 1, 2 ...) .
l
(6.44), (6.45). ( x ) = 0
D j = 0, C j =

2
l

f ( x ) sin l
1

jx1dx1 .

U j ( x , t ) , (6.39).

U j ( x , t ) = sin k j xC j cos ak j t ,
T
=
p
T.
a =

H
- p cos

x =

l
,
2

l
U j , t = sin jC j cos j t ,
2
2
j =

a
j - , -1.
l

l
= 0 , . .
, () U j , t
2
j = 2 , 4 ...
sin

j
2

j=1, 3... = 1 ,

l
U j , t
2

j =1, 3 ... =

sin

j
2

j= 2 , 4 ... =

0.

C j cos j t .

, C j . k j , j C j . . 6.1.
k j , j C j

6.1

j
kj

1
0,063

3
0,188

5
0,314

7
0,44

9
0,565

j , c-1

8,35

25,06

41,77

58,48

75,18

Cj ,

-0,117

-0,0043

-0,00074

-0,00018

-0,000036

Cj ,

-0,-86

-0,003

-0,00068

-0,00025

-0,00018

, Cnj
. (6.24) H H1 f n ( x1 ) = U n ( x1 ) U n1 ( x1 ) .
n , . 0,083 . Cnj . 6.1.
, () 0,117/0,083 = 1,41 .
, . 6.19. 0,117/0,0043 = 27 . 6.19 .

202

. 6.19. ,
, , . 3, 5, 7 9
. 6.20. 25 .

. 6.20. , ,
, , ,
.
. ,
, , .

6.3.2.
(6.40) . , j.

U ( x , t ) = sin k x C cos a t + D sin a t .

l
l

203

6.3 , U ( x,0) = f ( x ) ,

U
t

t =0

= ( x ) = 0

D = 0; C = f ( x) sin xdx .
l 0
l
l

l
2
f, , (6.25)
, x =

U ( x ,0) =

4f
x ( l x) .
l2

f =
U ( x ,0) =

1 gp 2
l , (6.24)
8 H

gp
x( x l ) ,
H

(6.25). f ( x) = U ( x ,0) , C
l

C=

2 4f

32
4 gp 2
x dx = 3 f = 3
l .
2 x ( l x ) sin

l 0 l
l

U ( x , t ) = C sin k x cos a

t.
l


U ( x , t ) = A ( x ) cos t ,
A( x ) = C sin kx =

(6.46)

32

x - x;
3 f sin

a
- , -1.
l
H
a =
- ,
p
=

-1.
32
l
l
A = 3 f = 1,032 f . , , 2

2
f. ,
. . , f, , 1gp 2
A = f =
l .
8 H
x =

204

(6.46)
U ( t ) = f cos t .

(6.47)

, (6.47) U + 2U = 0
t = 0; U = f ; U = 0 . ,
C = m 2 . , , , m = pl
l
x = . gm, f, . . gm = cf.
2
c - ,
gm
H
1gp 2
=8 .
-1. f =
l , c =
f
l
8 H
, ,
m, , c
mU cU = 0,

U 2U = 0,
=

c
8
=
m
l

H
p

= 111
, . 8
1,032 f, -
f.
( , , . .), 11
%.
, 3, 4,
.

Оценить